Hungary : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Hungary. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Hungary's several consecutive years of high growth and debt reduction. The pickup in growth was supported by high use of EU funds, a favorable external environment, and accommodative monetary and fiscal policies. However, despite robust private sector consumption, GDP growth temporarily slowed in 2016 to an estimated 2 percent, mainly because of a decline in investment. Output growth is projected to accelerate to about 2.9 percent in 2017. The recovery in EU funds disbursement and related investment, together with planned projects in the automotive industry, will be the main drivers of growth.